The Role of Besifloxacin in the Treatment of Bacterial Conjunctivitis. (May 2014) - Mahvan, Tracy D.; Hornecker, Jaime R.; Buckley, Whitney A.; Clark, Suzanne
Objective: To evaluate the role of besifloxacin in bacterial conjunctivitis treatment.Data Sources: Searches were made on MEDLINE/PubMed and EMBASE (January 2007 to January 2014) using the terms besifloxacin and Besivance . References from these publications were reviewed for additional resources. Additional information was collected from Bausch & Lomb, the manufacturer of Besivance;www.clinicaltrials.gov ; and American Academy of Ophthalmology.Study Selection and Data Extraction: English-language documents were reviewed for pharmacology, pharmacokinetics, efficacy, and safety, with priority on clinical trials.Data Synthesis: Three large randomized controlled clinical trials established the safety and efficacy of besifloxacin ophthalmic suspension 0.6% compared with placebo or active comparator (moxifloxacin ophthalmic solution 0.5%) given 3 times a day for 5 days for acute bacterial conjunctivitis (BC) treatment. Compared with placebo, besifloxacin had clinically superior bacterial eradication rates and was noninferior to moxifloxacin. Besifloxacin was compared with placebo in 2 randomized, placebo-controlled trials, dosed twice a day for 3 days. Superior efficacy was seen compared with placebo, which supports the shorter dosing schedule. Ophthalmic besifloxacin is well tolerated; the most common adverse effect (conjunctival redness) occurred in 2% of patients. Adverse effects in 1% to 2% of patients included blurred vision, eye pain, eye irritation, eye pruritus, and headache.Conclusion: Besifloxacin 0.6% ophthalmic suspension 3 times a day for 5 days is safe and effective for BC. Twice-a-day dosing for 3 days was also effective—a simplified regimen compared with other fluoroquinolones. Disadvantages include price and lack of a generic. Further evaluation is needed to evaluate comparative efficacy among other ocular fluoroquinolones and unlabeled uses.